Functions of nonsuicidal self-injurious behavior in Russian patients with suicidal ideation - Zinchuk, Mikhail; Kustov, Georgii; Popova, Sofya; Mishin, Ilya; Voinova, Nadezhda; Gersamija, Anna; Yakovlev, Alexander; Guekht, Alla (Frontiers in Public Health, 2023)
Introduction: Nonsuicidal self-injurious behavior (NSSI) is an important risk factor for future suicide attempts. Previous research has identified a number of motivations for engaging in NSSI. The aim of the present study was to translate the Inventory of Statements About Self-Injury (ISAS) into Russian and then to evaluate its psychometric properties in a sample of patients with non-psychotic mental disorders and suicidal ideation (SI). Other aims were to determine the prevalence of specific NSSI functions in this population and to assess the relationship between different NSSI functions and clinical and psychological parameters. Participants and methods: The study was conducted at the largest center for non-psychotic mental disorders in Moscow. All admitted patients with both NSSI and SI completed the Russian version of the ISAS-II, underwent the Self-Injurious Thoughts and Behaviors Interview, and completed the Personality Inventory for DSM-5 and ICD-11 Brief Form Plus-Modified, the Beck Depression Inventory, and the State-Trait Anxiety Inventory. Results: A total of 614 patients were included in the study. 543 (88.4%) patients were assigned female at birth with a mean age of 24.86 (7.86) years. Factor analysis supported a two-factor structure (Intrapersonal and Interpersonal) of the Russian version of the ISAS-II, but in contrast to the original study, the "Marking distress" function loaded more strongly on the Interpersonal factor. In people with non-psychotic mental disorders and SI, Interpersonal functions of NSSI are associated with more severe depressive symptoms (r=0.34), 12-month history of NSSI (r=0.30), higher number of NSSI methods (r=0.41), likelihood of future NSSI (r=0.35) and psychoticism (r=0.32). Conclusions: The Russian version of the ISAS-II is a valid and reliable instrument for assessing NSSI functions in a population at high risk for suicide attempts. Interpersonal functions are associated with a number of unpleasant clinical and psychological features.